CAPACITY TO ENDURE A SUSTAINABLE FUTURE: POINT OF VIEW OF HIGHER EDUCATION INSTITUTIONS - Triwacananingrum, Wijaya (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2025)
There are currently many institutions, industries (corporations), as well as educational institutions facing performance and sustainability problems. The demand for productive performance is a necessity to excel or at least survive in difficult times like now, especially due to the pandemic. The important things are the role of students in understanding and implementing sustainability, the role of management in implementing governance and the role of lecturers in the tridharma to maintain sustainability. It is deemed necessary that we lecturers as part of community service (Pengabadian Kepada Masyarakat/PKM) want to carry out activities at a university in North Sumatra. This activity will discuss how to socialize sustainability in higher education institution settings, how to improve performance, especially in relation to the tridharma of higher education institution, as well as equip students to learn about corporate cases and the role of governance to achieve sustainability in an institution. This Community Service (PKM) was carried out at the Surya Nusantara Adventist College in North Sumatra. The response to this event was very good considering the benefits for students, lecturers, staff, and management. This was reflected in the response during the event and the response to the results of filling in the questionnaire.